2017
DOI: 10.1371/journal.pone.0173463
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of physical activity and walking in an early stage after stroke or acquired brain injury

Abstract: BackgroundPhysical activity has been established as being highly beneficial for health after stroke. There are considerable global efforts to find rehabilitation programs that encourage increased physical activity for persons with stroke. However, many persons with stroke or acquired brain injury do not reach recommended levels of physical activity and increased knowledge about why is needed. We aimed to explore views and experiences of physical activity and walking among persons with stroke or acquired brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(82 reference statements)
3
29
2
2
Order By: Relevance
“…However, no relationship between season and steps indicates that more research is needed to determine if the significant step-complexity relationship could be utilized to motivate patients based on activity intensity as a way to increase activity amount during seasons in which weather may pose a barrier to activity. Interestingly, stroke survivors have been found to self-report "bad weather" as a barrier to the amount of physical activity performed, but especially the kind of unfavorable conditions that involve precipitation and increased risk of falling (Törnbom et al, 2017), but that relationship was not shown in our data; we did not see an effect of precipitation on walking activity. Perhaps the lack of precipitation relationship may mean the effect of weather may be more related to temperature; spring temperatures are mild, whereas winter temperatures are cold in the study population's region (Climate-Data.org).…”
Section: Discussioncontrasting
confidence: 83%
“…However, no relationship between season and steps indicates that more research is needed to determine if the significant step-complexity relationship could be utilized to motivate patients based on activity intensity as a way to increase activity amount during seasons in which weather may pose a barrier to activity. Interestingly, stroke survivors have been found to self-report "bad weather" as a barrier to the amount of physical activity performed, but especially the kind of unfavorable conditions that involve precipitation and increased risk of falling (Törnbom et al, 2017), but that relationship was not shown in our data; we did not see an effect of precipitation on walking activity. Perhaps the lack of precipitation relationship may mean the effect of weather may be more related to temperature; spring temperatures are mild, whereas winter temperatures are cold in the study population's region (Climate-Data.org).…”
Section: Discussioncontrasting
confidence: 83%
“…19 However, stroke survivors face considerable barriers to regular engagement in exercise. 20,21 Self-report data from the North-East Melbourne Stroke Incidence Study show that only 18% of stroke survivors are exercising regularly at five years after stroke. 22 Reducing time spent in uninterrupted sitting by introducing frequent short bouts of light-intensity physical activity during the day may be an alternative therapeutic target rather than, or in addition to, a program of moderate-intensity exercise.…”
Section: Introductionmentioning
confidence: 99%
“…As compensation is often insufficient or inefficient, patients tend to drag the hemiparetic foot across the ground with a high risk of falls [8, 9]. Additionally, the abnormal gait pattern leads to slower walking speed and, together with the increased risk of fall [10], they cause a reduced feeling of safety, necessitating the use of walking aids [11]. Compensatory mechanisms may also cause additional physical defects, including overuse symptoms due to increased activity in other muscle groups (such as tibialis posterior, flexor hallucis and digitorum, semitendinosus and semimembranosus) [12].…”
Section: Introductionmentioning
confidence: 99%